THE EFFECTIVENESS OF COMMUNICATIVE LANGUAGE TEACHING METHOD TO ENHANCE THE STUDENTS’ MOTIVATION IN INCREASING THEIR TOEFL SCORE - Martono, Eko (Language Circle: Journal of Language and Literature, 2013)
STIEPARI students’ achievement was found to have declined during 2008 - 2010. Almost all language skills were affected. One attempt to rectify the problem was the creation of a program called STIEPARI Language Course (SLC). The natures of the data in this research were quantitative and qualitative. The quantitative data were taken from the post-test TOEFL scores of 30 STIEPARI students. The 30 students were divided into 2 groups, Experimental Class and Control Class. Experimental Class was taught using Communicative Language Teaching (CLT) method in the teaching learning process; on the other hand, Control Class was taught without using CLT. The qualitative data were taken from student comments on the STIEPARI Language Course (SLC). From the t-test analysis, the result shows that there is a significant difference between the mean score of post-test of the Experimental Class and the mean score of post-test of the Control Class. This result shows that, statistically, the Communicative Language Teaching (CLT) method is an effective method to enhance students’ motivation in increasing TOEFL score. It should be mentioned, however, that TOEFL scores should be interpreted with care. To summarize students’ feedback on the STIEPARI Language Course (SLC), in general, both the Experimental Class and the Control Class learned a lot from the SLC. This comment is supported by the increase in TOEFL score.